Educational institutions in the Islamic Maghreb through the book Dictionary of Countries by Yakut Al-Hamawi - Saleh Al-Mohammadi, Othman Abdul-Aziz; Jassim Al- Mohammadi, Haider Ahmed (Journal of Tikrit University for Humanities, 2023)
The scientific movement in the Islamic Maghreb was characterized by activity, stability, and prosperity. It was of a religious nature in most cases. This is what made it spread and take a wide field, in addition to the great efforts made by the imams in spreading science after they realized the importance of educational institutions in consolidating the features of Islamic law. Books, mosques and linking in the dissemination of science.